SURVIVAL OF CORAL TRANSPLANTATION USING SPIDER MEDIA ON SAMALONA ISLAND, MAKASSAR - Arwin Arwin; Israwahyudi Israwahyudi; Rahmat Dwi Febrianto; Jusuwa Jusuwa (Universitas Mataram, 2025)
Coral reef ecosystems in coastal areas and on small islands, such as Samalona Island, play a vital role in fisheries and tourism. One method of coral reef conservation in Indonesia is the use of spider webs. This study aimed to analyze the survival and growth rate of coral reef transplants using the spider web method on Samalona Island from January to December 2024. Field data were obtained by measuring the length of coral fragments monthly. The results showed that coral seedling mortality was highest in the first quarter (27.05%) and lowest in the fourth quarter (1.44%). The highest growth rate was recorded in the fourth quarter (3.77 cm), with an average monthly growth rate of 0.88 cm.